REALISING THE CHILD’S RIGHTS IN EARLY CHILDHOOD IN THE CONTEXT OF CHILDREN’S SOCIAL PARTICIPATION: THE CASE OF THE CHILD’S RIGHT TO A FAMILY - TURCZYK, MAŁGORZATA (Society Register, 2021)
The article presents the need to make the culture of children's rights fundamental from the earliest years of their lives, given the idea of children's social participation. Creating and practising such a culture throughout childhood is a task that requires not only a thorough knowledge of the child’s rights among both parents and teachers but also the wider acceptance of these ideas and the creation of the right environment for sharing and speaking up for them both at home and in early education settings. The academic and colloquial discourse on parental practices and institutional childcare often overlooks the dimension/significance of recognising children's participation in safeguarding their human rights. Meanwhile, the processes of early normative socialisation are of great importance to their development and their future attitudes towards law in general and towards their human rights and others' rights. Social participation is where the child can experience his or her rights and learn about respecting others' rights. With this in mind, a question must be asked about how children's rights are realised in early childhood in the context of their participation in the socialisation process. The author uses the example of the child’s right to a family as a lens to observe how the idea of the children’s participation in securing children’s rights may be realised or violated. The article is based on an analysis of the subject's literature, in which legal discourse and teachings on child-rearing and early education are used as the interpretative context.